Pitch Lake, Brighton, Trinidad - Bryant (My University, 2010)
This is a photograph of the pitch lake, at Brighton, south west Trinidad. There is a pond on the pitch lake at left and patches of short verdant vegetation are growing on its surface. In the background there is a long single story building with a red roof, a few trees and an oil storage tank.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Brighton; Cities and towns--Trinidad and Tobago--La Brea; Asphalt industry--Trinidad and Tobago; Pitch; Buildings--Trinidad and Tobago; Asphalt--Trinidad and Tobago; Ponds--Trinidad and Tobago; [1920]; Pitch Lake, The (La Brea)